Endophthalmitis with bilateral deafness from disseminated Streptococcus suis infection. Issue 2 (26th February 2019) - Rayanakorn, Ajaree; Katip, Wasan; Lee, Learn Han; Oberdorfer, Peninnah
Abstract : Streptococcus suis is a Gram-positive cocci bacterium that are found mainly in pigs and can be transmitted to human through pigs or pork exposure. The disease is mainly found among occupations involving swine contact in western countries whereas in Asia the disease is usually contracted through raw pork consumption. In this case report, we present a case of a middle-aged Thai man who acquired the infection from raw pork consumption. He presented with endogenous endophthalmitis with infective spondylodiscitis, sepsis and meningitis and later developed blindness of the right eye and permanent bilateral hearing loss disseminated from S. suis infection. Our report suggests that S. suis infection be considered as a causative factor in patient presenting with established clinical symptoms and predisposing factors. Cultural habit of eating raw pork should be taken into account especially in Asian countries.